Estimation of Vitamin D Levels in Women with Carpal Tunnel Syndrome (with and without Diabetes) (Medico Legal Update, 2020)
Objective: Vitamin D is a an important vitamin which is effect on several system of human body, in thisstudy we determination serum levels of vitamin D in women patients with carpal tunnel syndrome (CTS)and investigation the relation between vitamin D and diabetes on CTS patients.Materials and Method: Subjects of this study enrolled 53 women (33 patients and 20 control), their agedrange between (30-50) year. The patients were selected from attendee of out- patient Neurology clinic ofAl- Imam Sadiq teaching Hospital, Hilla city, Iraq, in the period from December 2018 to April 2019. Bloodsamples were taken from subject to determination vitamin D levels.Results: The present study shows a significant (p